Saadoe'ddin Djambek Dan Pemikirannya Tentang Hisab - Susiknan Azhari (Al-Jami'ah Research Centre, 1998)
It is worth to recognize that Indonesia, as a nation with its diversity including the diversity of the methods of hisab (method of measuring the sun and the moon positions), needs openness and objective thinking. Only with both openness and objective thinking, everyone belongs to a certain school of thinking understands others' methods for their differences and similarities. Through understanding the different methods an appreciation to other methods will come to rise: This paper tries to analyses Saadoe’ddin Djambek thought of hisab which covers hisab on queblat (Ka'ba/direction), time for prayers and the beginning of a new month. Furthermore, this paper focuses on the characteristics of his concepts of hisab, approaches and method used in formulating bisab theories, and the influence of astronomy on his way to build hisab paradigm. After analysing his works, it can be concluded that Djambek's thought of hisab is a creative synthesis that combines the methods of hisab experts and Djalaluddin from hisab experts and Prof. Dr. G.B. Van Al-bada from astronomers. Saadoe'ddin Djambek has been influencing hisab thought in Indonesia, although there are some problems that often emerge.